Recent advances in ternary Z-scheme photocatalysis on graphitic carbon nitride based photocatalysts - Zhou, Dantong; Li, Dongxiang; Chen, Zhi (Frontiers in Chemistry, 2024)
Due to its excellent photocatalytic performance over the last few years, graphitic-like carbon nitride (g-C3N4) has garnered considerable notice as a photocatalyst. Nevertheless, several limitations, including small surface area, the rates at which photo-generated electrons and holes recombine are swift, and the inefficient separation and transport of photoexcited carriers continue to impede its solar energy utilization. To overcome those limitations in single-component g-C3N4, constructing a heterogeneous photocatalytic system has emerged as an effective way. Among the various studies involving the incorporation of hetero composite materials to design heterojunctions, among the most promising approaches is to assemble a Z-scheme photocatalytic configuration. The Z-scheme configuration is essential because it facilitates efficient photocarrier separation and exhibits superior redox ability in separated electrons and holes. Moreover, ternary composites have demonstrated enhanced photocatalytic activities and reinforced photostability. Ternary Z-scheme heterostructures constructed with g-C3N4 possess all the above-mentioned merits and provide a pioneering strategy for implementing photocatalytic systems for environmental and energy sustainability. A summary of the latest technological advancements toward design and fabrication in ternary all-solid-state Z-scheme (ASSZ) and direct Z-scheme (DZ) photocatalysts built on g-C3N4 is presented in this review. Furthermore, the review also discusses the application of ternary Z-scheme photocatalytic architecture established on g-C3N4.